EXISTENCE OF LAND PECATU IN EAST LOMBOK (Case Study In the village Sukadana district. Terara in East Lombok) - Amelia, Mirza (Jurnal IUS, 2015)
Soil is a natural resource that is essential for human life, for the country has provided a firm foundation as stipulated in article 33 paragraph (3) of the 1945 Constitution, on the basis of the provisions that it gives birth to Act No. 5 of 1950 the Act was not complete calls on Pecatu ground, but can be categorized as customary rights because it is still governed by customary law provisions. Besides, the recognition of land Pecatu in the UUPA must meet two requirements, namely the existence and implementation along by the fact still exist in an area. Itâs function is intended as a revenue village chief and other officials.Keywords: Existence, Land Pencatu, UUPA.